Uma reflexão sobre terminalidade assistida em contexto de vulnerabilidade social - Souza, Helenira Porfírio de (2021)
The assistance in dying consists of promoting relief from pain or any discomforts coming from the process of dying, which might last for a considerable amount of time, such as months or years. Aiming to understand this assistance paid to the dying, in a configuration apparently atypical from the ones described in the specialized literature, a survey was carried out, based on biographic data of the founder of the institution and also of people who are, in any manner, involved with the modality of aiding in end-of-life situations named as Palliative Care, which the institution observed presents itself as an adept. The change in paradigm at the assistance in dying in Brazil was explored as a reference to the construction of the aforementioned aid in dying and to the national and international contributions for the promotion of death under favorable conditions. The experiences found, demonstrate the impossibility of the application of the theory under determined conditions, such as the accompaniment of death of people assisted by the State in life. This fact explains and justifies the initiative of offering aid to people under conditions that are incompatible with life, granting them at least the possibility of a proper closure to life within the material conditions and the context in which the institution and its idealizer are inserted.